ORIENTALISM IN THE WESTERN CULTURAL INDUSTRY - Araújo, Mayara (2024)
China’s economic strength is an undeniable fact. Despite its growth, the imagery about the country remains linked to a Western perspective that does not seem to be updated. We question how China is represented in Western audiovisuals, and the hypothesis is that the nation is presented in an orientalist way through the western lens and little interested in its sociocultural reality. We search, then, intertwine notable cases of China’s representation in Western audiovisual with the geopolitical dynamics of its time.